ECONOMIC AND SOCIAL IMPACT OF MIGRATION - Thomson Sitompul (Universitas Pelita Harapan Medan Campus, 2023)
The previous study in the migration topic was focused to see its impact to the economic and social scope only to the origin country. The purposes of this study are to know how does international migration impact the economic aspects of origin country and destination country and how does international migration impact the social aspects of the origin country and destination country. The data in this study are based on books and journals that are relevant to the author's research. The data analysis technique used in this study is qualitative data analysis where in this study the opinions expressed by experts regarding instructional media are used as a basis for strengthening the author's arguments in analyzing the effects of migration on the economy and social. The economic impact to the country of origin can be seen through remittances while to the destination country can be seen through GDP, unemployed migrants and competition in looking for work. The social impact to the country of origin can be seen through by the migrant families who are left behind, which causes the psychological cost while to the destination country can be seen through the integration of migration.